2019
DOI: 10.4310/mrl.2019.v26.n5.a11
|View full text |Cite
|
Sign up to set email alerts
|

Bordered theory for pillowcase homology

Abstract: We construct an algebraic version of Lagrangian Floer homology for immersed curves inside the pillowcase. We first associate to the pillowcase an algebra A. Then to an immersed curve L inside the pillowcase we associate an A∞ module M (L) over A. Then we prove that Lagrangian Floer homology HF (L, L ) is isomorphic to a suitable algebraic pairing of modules M (L) and M (L ). This extends the pillowcase homology construction given a 2-stranded tangle inside a 3-ball, if one obtains an immersed unobstructed Lagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(115 reference statements)
1
1
0
Order By: Relevance
“…In words, the Khovanov homology of the link arising as the union of a tangle T with the mirror of a tangle V can be recovered, up to tensoring with a particular two dimensional vector space, as the cohomology of the space of morphisms between the twisted complexes we associate to V and T , respectively. We should point out that similar results in these directions, and more precise comparisons with bordered Floer homology, have been obtained independently by Kotelskiy [21,20].…”
Section: Introductionsupporting
confidence: 81%
“…In words, the Khovanov homology of the link arising as the union of a tangle T with the mirror of a tangle V can be recovered, up to tensoring with a particular two dimensional vector space, as the cohomology of the space of morphisms between the twisted complexes we associate to V and T , respectively. We should point out that similar results in these directions, and more precise comparisons with bordered Floer homology, have been obtained independently by Kotelskiy [21,20].…”
Section: Introductionsupporting
confidence: 81%
“…In the context of instanton knot Floer homology, for 4-ended tangles, this leads to representation theoretic constructions of immersed curves R π (T ) and R π (T ) on the pillowcase due to Hedden, Herald and Kirk [HHK14,HHK18]. The first author extended this construction algebraically [Kot19]. In Heegaard Floer homology, Auroux [Aur10a,Aur10b] and Lekili and Perutz [LP11] suggested that the correct moduli space for the invariant of a compact oriented 3-manifold M with ∂M = Σ g and a basepoint z ∈ Σ g should be Sym g (Σ g z).…”
Section: T (∂I ∂I)mentioning
confidence: 99%